Preparation method and structure of perovskite battery
By adding acid solution and lead-tin perovskite precursor solution to the hole transport layer of lead-tin perovskite solar cell, the structure of the hole transport layer and lead-tin perovskite film layer is optimized, and the low conductivity is solved and the problem of insufficient stability significantly improves the photoelectric conversion efficiency and long-term stability of the battery.
Patent Information
- Application Number
- CN202411542198.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
AI Technical Summary
In existing high-performance lead-tin perovskite solar cells, the hole transport layer has low conductivity and insufficient stability, which limits the photoelectric conversion efficiency and long-term stability of the battery.
The optimized first hole transport layer is formed by coating the PEDOT:PSS solution and acid solution on the conductive substrate and annealing; then the lead-tin perovskite precursor solution is coated on this basis and the anti-solvent is performed Treatment and annealing treatment to form a lead-tin perovskite film layer.
The crystal crystallinity and crystal orientation of the lead-tin perovskite film layer are significantly optimized, the adaptability of the hole transport layer and the lead-tin perovskite film layer is enhanced, and the power conversion efficiency and long-term stability of the perovskite battery are improved. sex.
Smart Images

Figure CN119451525A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells and relates to a preparation method and structure of a perovskite cell. Background Art
[0002] The field of solar cells is developing rapidly. The highest certified efficiency of silicon solar cells has gradually approached its Shockley-Queisser (SQ) efficiency limit, and it is becoming increasingly difficult to further improve the efficiency. In order to break this bottleneck, scientists are actively exploring new solar cell structures to seek breakthroughs. Perovskite materials, due to their unique crystal structure and adjustable band gap, have shown great application potential in the field of solar cells, especially in tandem cell technology.
[0003] By superimposing two perovskite absorption layers with different band gaps, all-perovskite tandem solar cells not only effectively broaden the absorption spectrum of the cell, but also significantly reduce thermal relaxation losses, and are expected to break through the SQ efficiency limit of 33.7% and achieve higher power conversion efficiency. Among them, the lead-tin mixed perovskite material with a band gap range of 1.17-1.3eV has become an ideal choice for the bottom material of tandem solar cells due to its unique physical and chemical properties. By precisely controlling the composition and morphology of lead-tin perovskite and combining it with a wide bandgap perovskite material, an efficient all-perovskite tandem solar cell can be prepared. Therefore, the development of efficient and stable lead-tin mixed perovskite solar cells is of vital importance to promoting the further development of all-perovskite tandem solar cell technology.
[0004] However, many high-performance lead-tin perovskite solar cells currently generally use poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS) to form a hole transport layer, but the formed hole transport layer has problems such as low conductivity and insufficient stability, which seriously limits the overall photoelectric conversion efficiency and long-term stability of the battery structure.
[0005] Therefore, how to provide a new preparation method and structure of perovskite cells to overcome these limitations and improve the overall performance of the cells has become an important technical problem that needs to be urgently solved by those skilled in the art.
[0006] It should be noted that the above introduction to the technical background is only for the convenience of providing a clear and complete description of the technical solutions of the present application and for the convenience of understanding by those skilled in the art. It cannot be considered that the above technical solutions are well known to those skilled in the art simply because they are described in the background technology section of the present application. Summary of the invention
[0007] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a method for preparing a perovskite cell and a structure thereof, so as to solve the problems of low conductivity and insufficient stability of the hole transport layer formed in the prior art, which leads to low photoelectric conversion efficiency of the cell and limited long-term stability.
[0008] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a perovskite battery, comprising the following steps:
[0009] Providing a conductive substrate, and pre-treating the conductive substrate;
[0010] Applying the PEDOT:PSS solution and the acid solution separately or pre-mixing them on the conductive substrate, and performing annealing treatment to form a first hole transport layer;
[0011] A lead-tin perovskite precursor solution of a certain concentration is prepared, the lead-tin perovskite precursor solution is coated on the first hole transport layer, and the lead-tin perovskite precursor solution is subjected to an anti-solvent treatment, and then an annealing treatment is performed to form a lead-tin perovskite thin film layer;
[0012] forming a first electron transport layer on the lead-tin perovskite thin film layer;
[0013] A metal electrode layer is formed on the first electron transport layer.
[0014] Optionally, the PEDOT:PSS solution and the acid solution are coated on the conductive substrate in a pre-mixed manner, wherein the acid solution is added to the PEDOT:PSS solution in a preset ratio to form a mixed solution, and then the mixed solution is coated on the conductive substrate.
[0015] Optionally, the PEDOT:PSS solution and the acid solution are coated on the conductive substrate in a separate application manner, wherein after the PEDOT:PSS solution is coated on the conductive substrate, the acid solution is applied on the conductive substrate coated with the PEDOT:PSS solution.
[0016] Optionally, the acid solution includes any one of formic acid, acetic acid, oxalic acid, citric acid, malic acid, crotonic acid and caffeic acid.
[0017] Optionally, a first passivation layer is further formed between the lead-tin perovskite thin film layer and the first electron transport layer.
[0018] Optionally, a first modification layer is further formed between the first electron transport layer and the metal electrode layer.
[0019] Optionally, before forming the first hole transport layer, the method further includes forming a top battery structure layer on the conductive substrate, and the PEDOT:PSS solution and the acid solution are coated on the surface of the top battery structure layer.
[0020] Optionally, the formation of the top battery structure layer comprises the following steps:
[0021] forming a second hole transport layer on the conductive substrate;
[0022] forming an interface modification layer on the second hole transport layer;
[0023] A perovskite precursor solution of a certain concentration is prepared, the perovskite precursor solution is coated on the interface modification layer, the perovskite precursor solution is subjected to an anti-solvent treatment, and then an annealing treatment is performed to form a perovskite thin film layer, wherein the band gap width of the perovskite thin film layer is greater than the band gap width of the lead-tin perovskite thin film layer;
[0024] forming a second electron transport layer on the perovskite thin film layer;
[0025] An interconnection layer is formed on the second electron transport layer.
[0026] Optionally, a second modification layer is formed between the second electron transport layer and the interconnect layer.
[0027] The present invention also provides a perovskite battery structure, and the perovskite battery structure is obtained by using any one of the above-mentioned perovskite battery preparation methods.
[0028] As described above, the present invention provides a method for preparing a perovskite battery and its structure, which not only achieves the optimization treatment of the PEDOT:PSS hole transport layer by adding acid during the formation of the first hole transport layer, but also enhances the compatibility of the first hole transport layer with the upper lead-tin perovskite film layer, and significantly optimizes the crystal crystallinity and crystal orientation of the lead-tin perovskite film layer, eliminating the problems of excessive gaps between crystals, fine grains, and poor crystallinity after perovskite crystallization caused by the presence of impurities or excessive lead iodide and tin iodide, thereby effectively improving the power conversion efficiency of the perovskite battery. The preparation method of the present invention is simple and easy, significantly improves the overall performance of the perovskite battery, and can be widely used in photovoltaic power generation, photoelectric detection and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Shown is a process flow chart of the method for preparing the perovskite battery of the present invention.
[0030] Figure 2It is a schematic diagram showing the cross-sectional structure of a perovskite cell formed in Example 1 according to the method for preparing a perovskite cell of the present invention.
[0031] Figure 3 Shown is an electron microscope photograph of a cross section of a lead-tin perovskite thin film layer prepared on a first hole transport layer formed from a PEDOT:PSS solution in a comparative example.
[0032] Figure 4 Shown is an X-ray diffraction (XRD) pattern of a lead-tin perovskite thin film layer prepared on a first hole transport layer formed from a PEDOT:PSS solution in a comparative example.
[0033] Figure 5 Shown is the current density and voltage characteristic curve of the perovskite battery prepared in the comparative example.
[0034] Figure 6 Shown is an electron microscope photograph of a cross section of the lead-tin perovskite thin film layer prepared on the first hole transport layer in a specific example of the preparation method of the perovskite cell of the present invention.
[0035] Figure 7 Shown is the XRD spectrum of the lead-tin perovskite thin film layer prepared on the first hole transport layer in a specific example of the preparation method of the perovskite battery of the present invention.
[0036] Figure 8 Shown is a current density and voltage characteristic curve of the perovskite cell formed in a specific example of the preparation method of the perovskite cell of the present invention.
[0037] Fig. 9 Shown is a comparison chart of the power conversion efficiency of perovskite cells prepared according to a specific example of the present invention and a comparative example.
[0038] Fig.10 It is a schematic diagram showing the cross-sectional structure of a perovskite cell formed in Example 2 according to the method for preparing a perovskite cell of the present invention.
[0039] Component number description
[0040] 1. Tandem Perovskite Cell
[0041] 11 Lead-tin perovskite battery
[0042] 111 Conductive substrate
[0043] 112 first hole transport layer
[0044] 113 Lead-tin perovskite thin film layer
[0045] 114 First passivation layer
[0046] 115 First electron transport layer
[0047] 116 First Modification Layer
[0048] 117 Metal electrode layer
[0049] 12 Top battery structure layer
[0050] 121 Second hole transport layer
[0051] 122 Interface modification layer
[0052] 123 Perovskite thin film layer
[0053] 124 Second electron transport layer
[0054] 125 Second modification layer
[0055] 126 Interconnect Layer
[0056] Steps S1 to S5 DETAILED DESCRIPTION
[0057] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0058] See also Figures 1 to 10 It should be noted that the illustrations provided in this embodiment are only used to illustrate the basic concept of the present invention in a schematic manner, and the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0059] Embodiment 1
[0060] The present invention provides a method for preparing a perovskite battery. Figure 1 , shown as a process flow chart of the method, comprising the following steps:
[0061] S1: providing a conductive substrate and pre-treating the conductive substrate;
[0062] S2: applying the PEDOT:PSS solution and the acid solution separately or pre-mixing them on the conductive substrate, and performing annealing treatment to form a first hole transport layer;
[0063] S3: preparing a lead-tin perovskite precursor solution of a certain concentration, coating the lead-tin perovskite precursor solution on the first hole transport layer, performing an anti-solvent treatment on the lead-tin perovskite precursor solution, and then performing an annealing treatment to form a lead-tin perovskite thin film layer;
[0064] S4: forming a first electron transport layer on the lead-tin perovskite thin film layer;
[0065] S5: forming a metal electrode layer on the first electron transport layer.
[0066] First, see Figure 2 , perform the step S1: provide a conductive substrate 111, and pre-treat the conductive substrate 111.
[0067] As an example, the conductive substrate 111 includes a rigid conductive substrate and a flexible conductive substrate.
[0068] Specifically, the rigid conductive substrate includes but is not limited to tin dioxide doped fluorine conductive glass (FTO), zinc oxide doped aluminum conductive glass (AZO), indium tin oxide conductive glass (ITO) and tungsten doped indium oxide (IWO), etc. The flexible conductive substrate includes but is not limited to indium tin oxide conductive polyethylene terephthalate (such as ITO-PET conductive plastic sheet), etc.
[0069] As an example, the process of pretreating the conductive substrate 111 includes: first, cleaning the conductive substrate 111 with deionized water and detergent to remove dust and other particulate matter on the conductive substrate 111, and then placing the conductive substrate 111 in isopropyl alcohol and acetone for ultrasonic cleaning in turn, each for 30 minutes, to remove oil-soluble impurities and water-soluble impurities on the conductive substrate 111.
[0070] As an example, after the pretreatment of the conductive substrate 111 , the method further includes performing plasma treatment or ozone treatment on the conductive substrate 111 to further clean and activate the surface of the conductive substrate 111 and improve the surface energy and adhesion of the conductive substrate 111 .
[0071] As an example, the time range of plasma treatment on the conductive substrate 111 is 3 to 8 minutes.
[0072] As an example, the time range of ozone treatment on the conductive substrate 111 is 10 to 30 minutes.
[0073] Please see again Figure 2 , performing the step S2: coating the PEDOT:PSS solution and the acid solution on the conductive substrate 111 by applying them separately or pre-mixing them, and performing annealing treatment to form a first hole transport layer 112 .
[0074] As an example, the acid solution includes any one of formic acid, acetic acid, oxalic acid, citric acid, malic acid, crotonic acid and caffeic acid.
[0075] As an example, the PEDOT:PSS solution and the acid solution are applied separately or pre-mixed on the conductive substrate 111 by any one of spraying, spin coating, drip coating, blade coating, roller coating, air knife coating and brush coating.
[0076] As an example, the PEDOT:PSS solution and the acid solution are coated on the conductive substrate 111 in a pre-mixed manner, wherein the acid solution is added to the PEDOT:PSS solution in a preset ratio to form a mixed solution, and then the mixed solution is coated on the conductive substrate 111.
[0077] As an example, the volume ratio of the acid solution to the PEDOT:PSS solution ranges from 0.01 to 0.05.
[0078] Specifically, in this embodiment, the acid solution is preferably formic acid. When preparing the mixed solution, formic acid is first added to the PEDOT:PSS solution at a volume ratio of 0.015, and then the mixed solution is ultrasonically treated using ultrasonic stirring technology to ensure that the formic acid and the PEDOT:PSS solution are fully mixed and evenly dispersed.
[0079] As an example, the PEDOT:PSS solution and the acid solution are coated on the conductive substrate 111 in a separate application manner, wherein after the PEDOT:PSS solution is coated on the conductive substrate 111, the acid solution is applied on the conductive substrate 111 coated with the PEDOT:PSS solution.
[0080] Specifically, in this embodiment, the conductive substrate 111 coated with the PEDOT:PSS solution and the acid solution is annealed in an inert gas environment, the temperature range of the annealing treatment is 100 to 300°C, and the time range of the annealing treatment is 5 to 20 minutes. The annealing treatment can improve the conductivity and density of the first hole transport layer 112 while removing the residual solvent, optimize the crystallinity of the first hole transport layer 112, and effectively improve the interface performance, reduce the charge recombination at the interface, thereby improving the overall performance of the battery.
[0081] As an example, the thickness of the first hole transport layer 112 is in the range of 10 to 30 nanometers. In this embodiment, the thickness of the first hole transport layer 112 is preferably 20 nanometers.
[0082] See also Figure 2 , execute the step S3: prepare a lead-tin perovskite precursor solution of a certain concentration, apply the lead-tin perovskite precursor solution on the first hole transport layer 112, and perform anti-solvent treatment on the lead-tin perovskite precursor solution, and then perform annealing treatment to form a lead-tin perovskite thin film layer 113.
[0083] As an example, preparing the lead-tin perovskite precursor solution includes the following steps:
[0084] Cesium iodide (CsI), methylamine iodide (MAI), formamidine iodide (FAI), lead iodide (PbI2) and stannous iodide (SnI2) were dissolved in a mixed solvent consisting of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) in a volume ratio of 1:3, and stirred until the mixture was uniform to obtain a CsI solution with a concentration range of 1 to 3 mol / mL. 0.05 FA 0.65 MA 0.3 Pb 0.5 Sn 0.5 I3 lead-tin perovskite precursor solution.
[0085] As an example, the coating method of coating the lead-tin perovskite precursor solution on the first hole transport layer 112 includes any one of spraying, spin coating, drop coating, doctor blade coating, roller coating, air knife coating and brush coating.
[0086] As an example, coating the lead-tin perovskite precursor solution on the first hole transport layer 112 and performing anti-solvent treatment on the lead-tin perovskite precursor solution includes the following steps:
[0087] The lead-tin perovskite precursor solution is coated on the first hole transport layer 112 and spin-coated at a rotation speed of 500-1500 rpm for 5-15 seconds, and then spin-coated at a rotation speed of 3500-4500 rpm for 30-50 seconds, and an anti-solvent is added dropwise 5-15 seconds before the end of coating.
[0088] As an example, the anti-solvent includes any one of chlorobenzene, ethyl acetate, dimethyl ethyl carbonate, ethanol and diethyl ether.
[0089] As an example, the volume ratio of the anti-solvent to the lead-tin perovskite precursor solution is in the range of 2 to 6. In this embodiment, the addition of the anti-solvent can effectively promote the uniform growth of the lead-tin perovskite crystals.
[0090] Specifically, in this embodiment, the temperature range of the annealing treatment performed after the anti-solvent treatment is 50 to 150° C., and the time range of the annealing treatment is 5 to 20 minutes.
[0091] See also Figure 2 , perform the step S4: forming a first electron transport layer 115 on the lead-tin perovskite thin film layer 113 .
[0092] As an example, a first passivation layer 114 is further formed between the lead-tin perovskite thin film layer 113 and the first electron transport layer 115. The first passivation layer 114 can effectively reduce the interface defects between the lead-tin perovskite thin film layer 113 and the first electron transport layer 115, inhibit non-radiative recombination, and improve the open circuit voltage (Voc) and power conversion efficiency (PCE) of the formed perovskite battery.
[0093] As an example, the method of forming the first passivation layer 114 includes any one of spray coating, spin coating, scraper coating, slit coating and thermal evaporation. In this embodiment, the first passivation layer 114 is preferably formed by spin coating.
[0094] As an example, the material of the first passivation layer 114 includes at least one of ethylenediamine dihydroiodide (EDAI), 1,3-diaminopropane dihydroiodide (PDADI), 4-methoxyphenethylammonium iodide (PEAI), phenethylammonium bromide (PEABr) and 4-trifluoromethylphenethylammonium chloride (CF3-PEACl).
[0095] In a specific example, the first passivation layer 114 is formed by spin coating a 0.5 mg / ml EDAI solution on the lead-tin perovskite thin film layer 113 .
[0096] As an example, the method of forming the first electron transport layer 115 includes any one of spray coating, spin coating, scraping, sputtering and evaporation. In this embodiment, the first electron transport layer 115 is preferably formed by spin coating.
[0097] As an example, the material of the first electron transport layer 115 includes 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), fullerene derivatives (PCBM), fullerene (C 60 ), tin dioxide (SnO2), titanium oxide and zinc oxide. In this embodiment, the first electron transport layer 115 is preferably formed by using a PCBM solution.
[0098] As an example, the concentration range of the PCBM solution is 10-30 mg / ml.
[0099] See also Figure 2 , perform the step S5: forming a metal electrode layer 117 on the first electron transport layer 115 .
[0100] As an example, a first modification layer 116 is formed between the first electron transport layer 115 and the metal electrode layer 117. The first modification layer 116 can effectively passivate the interface defects between the first electron transport layer 115 and the metal electrode layer 117, inhibit non-radiative recombination, and improve the photoelectric conversion efficiency.
[0101] As an example, the method of forming the first modification layer 116 includes at least one of spin coating, spray coating, printing, printing and scraping. In this embodiment, the first modification layer 116 is preferably formed by spin coating.
[0102] As an example, the material of the first modification layer 116 includes at least one of BCP, lithium fluoride (LiF), cesium carbonate (Cs2CO3), and 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBI). In this embodiment, it is preferred to use a supersaturated BCP solution to form the first modification layer 116.
[0103] Specifically, the method of forming the metal electrode layer 117 includes magnetron sputtering, evaporation, physical vapor deposition, chemical vapor deposition, metal compound vapor deposition, molecular beam epitaxy, atomic vapor deposition, atomic layer deposition or other suitable methods.
[0104] As an example, the material of the metal electrode layer 117 includes any one of gold, silver, aluminum, copper, nickel, carbon, and ITO.
[0105] As an example, the thickness of the metal electrode layer 117 is in the range of 80 to 180 nanometers.
[0106] At this point, a perovskite battery (lead-tin perovskite battery 11) is produced. In the preparation method of a perovskite battery provided in this embodiment, the first hole transport layer 112 is formed by using a PEDOT:PSS solution and an acid solution, the energy level structure of the first hole transport layer 112 is significantly optimized, and the matching between the first hole transport layer 112 and the lead-tin perovskite film layer 113 is enhanced. This improvement effectively reduces the transmission barrier of carriers between the first hole transport layer 112 and the lead-tin perovskite film layer 113, and improves the extraction efficiency and transmission of carriers. In addition, the introduction of the acid solution significantly improves the wettability and flatness of the first hole transport layer 112, so that the lead-tin perovskite precursor solution can be evenly spread on its surface, prompting the formation of a uniform and well-crystallized lead-tin perovskite film layer 113. At the same time, this improvement also provides a more uniform transmission path for the charge, reduces the scattering and loss during the transmission process, thereby significantly improving the overall performance of the perovskite battery.
[0107] The following is a comparative example and a specific example in the first embodiment of the present invention for comparison and explanation.
[0108] In one pair of ratios, the preparation of perovskite cells includes the following steps:
[0109] (1) First, an ITO conductive glass substrate with a length of 15 cm and a width of 15 cm was taken, and then the ITO conductive glass substrate was cleaned with deionized water and detergent to remove dust and other particles on the ITO conductive glass substrate. Then, the ITO conductive glass substrate was placed in isopropanol and acetone for ultrasonic cleaning in turn, and the cleaning was carried out for 30 minutes respectively to remove oil-soluble impurities and water-soluble impurities on the ITO conductive glass substrate. Afterwards, the ITO conductive glass substrate was treated with ozone using an ozone machine for 20 minutes to further clean and activate the surface of the ITO conductive glass substrate.
[0110] (2) 60 μL of PEDOT:PSS solution was drop-coated on the surface of the ITO conductive glass substrate and spin-coated at 4000 rpm for 30 seconds. Afterwards, the ITO conductive glass substrate was annealed at 200° C. for 10 minutes to solidify and form a first hole transport layer with a thickness of 20 nm.
[0111] (3) CsI, MAI, FAI, PbI2 and SnI2 were dissolved in a mixed solvent consisting of DMSO and DMF and stirred for 2 hours to form a CsI solution with a concentration of 1.8 mol / mL. 0.05 FA 0.65 MA 0.3 Pb 0.5 Sn 0.5 I3 lead-tin perovskite precursor solution, wherein the volume of DMSO is 0.25 mL and the volume of DMF is 0.75 mL. Next, take 50 μL of the Cs 0.05 FA 0.65 MA 0.3 Pb 0.5 Sn 0.5 The I3 lead-tin perovskite precursor solution was drop-coated on the first hole transport layer, and the Cs 0.05 FA 0.65 MA 0.3 Pb 0.5 Sn 0.5 I3 lead-tin perovskite precursor solution was spin-coated for 10 seconds to ensure uniform coverage of the surface of the first hole transport layer. After that, it was rotated at a speed of 4000 rpm for 40 seconds. When it was rotated to 30 seconds, 200 μL of chlorobenzene was added for anti-solvent treatment. Finally, annealing was performed at a temperature of 100°C and a time of 10 minutes to form a lead-tin perovskite thin film layer. Figure 3As shown in FIG. 1 , a lead-tin perovskite film layer is prepared on the first hole transport layer formed only by a PEDOT:PSS solution. The lead-tin perovskite film layer has poor crystallinity, loosely arranged crystals, large gaps between crystals, small grains, and a rough and uneven film surface. Figure 4 It can be seen from the XRD spectrum that the peak intensity of the lead-tin perovskite film layer is low, indicating that its crystallinity is also low, the crystal structure is not complete, and the grain orientation is poor.
[0112] (4) Dynamically spin-coat 0.5 mg / ml EDAI solution on the lead-tin perovskite film layer at a rotation speed of 4000 rpm to form a first passivation layer. Then, spin-coat 20 mg / ml PCBM solution on the first passivation layer at a rotation speed of 1500 rpm to form a first electron transport layer. Next, dynamically spin-coat an oversaturated BCP solution at a rotation speed of 4000 rpm to form a first modification layer. Finally, a silver electrode with a thickness of 130 nanometers is formed on the first modification layer by an evaporation method to prepare a perovskite battery. Figure 5 As shown, the power conversion efficiency (PCE) of the formed perovskite battery is 20.54%, and the open circuit voltage (V OC ) is 0.85V, the short-circuit current (J SC ) is 31.55mA / cm 2 , the filling factor (FF) is 76.32%.
[0113] In a specific example of the method for preparing a perovskite cell of the present invention, the following steps are included:
[0114] (1) First, an ITO conductive glass substrate with a length of 15 cm and a width of 15 cm was taken, and then the ITO conductive glass substrate was cleaned with deionized water and detergent to remove dust and other particles on the ITO conductive glass substrate. Then, the ITO conductive glass substrate was placed in isopropyl alcohol and acetone for ultrasonic cleaning in turn, and the cleaning was carried out for 30 minutes respectively to remove oil-soluble impurities and water-soluble impurities on the ITO conductive glass substrate. Afterwards, the ITO conductive glass substrate was treated with ozone using an ozone machine for 20 minutes to further clean and activate the surface of the ITO conductive glass substrate.
[0115] (2) Formic acid was added to the PEDOT:PSS solution at a volume ratio of 0.015 to form a mixed solution, and the mixed solution was ultrasonically treated for 3 minutes to ensure that the formic acid and the PEDOT:PSS solution were fully mixed. Subsequently, 60 μL of the mixed solution was drop-coated on the surface of the ITO conductive glass substrate and spin-coated at 4000 rpm for 30 seconds. Thereafter, the ITO conductive glass substrate was annealed at 200° C. for 10 minutes to solidify and form the first hole transport layer with a thickness of 20 nm.
[0116] (3) CsI, MAI, FAI, PbI2 and SnI2 were dissolved in a mixed solvent consisting of DMSO and DMF and stirred for 2 hours to form a CsI solution with a concentration of 1.8 mol / mL. 0.05 FA 0.65 MA 0.3 Pb 0.5 Sn 0.5 I3 lead-tin perovskite precursor solution, wherein the volume of DMSO is 0.25 mL and the volume of DMF is 0.75 mL. Next, take 50 μL of the Cs 0.05 FA 0.65 MA 0.3 Pb 0.5 Sn 0.5 The I3 lead-tin perovskite precursor solution was drop-coated on the first hole transport layer, and the Cs 0.05 FA 0.65 MA 0.3 Pb 0.5 Sn 0.5 I3 lead-tin perovskite precursor solution was spin-coated for 10 seconds to ensure uniform coverage of the surface of the first hole transport layer. Afterwards, it was rotated at a speed of 4000 rpm for 40 seconds. When the rotation reached 30 seconds, 200 μL of chlorobenzene was added for anti-solvent treatment. Finally, annealing was performed at a temperature of 100°C for 10 minutes to form the lead-tin perovskite thin film layer. Figure 6 As shown, in this example, after formic acid and PEDOT:PSS solution are used to form the first hole transport layer, the lead-tin perovskite film layer formed on the first hole transport layer exhibits excellent crystallization characteristics, the crystals are tightly arranged and of high quality, and the film surface is flat and uniform without obvious defects. Figure 7It can be seen from the XRD spectrum that the peak intensity of the lead-tin perovskite film layer is high and the peak shape is sharp and clear, which fully demonstrates that the lead-tin perovskite film layer has high crystallinity, complete crystal structure and good grain orientation. The crystal quality of the lead-tin perovskite film layer formed in this example is much higher than that of the lead-tin perovskite film layer formed in the comparative example.
[0117] (4) Dynamically spin-coat 0.5 mg / ml EDAI solution on the lead-tin perovskite film layer at a rotation speed of 4000 rpm to form a first passivation layer. Then, spin-coat 20 mg / ml PCBM solution on the first passivation layer at a rotation speed of 1500 rpm to form a first electron transport layer. Next, dynamically spin-coat an oversaturated BCP solution at a rotation speed of 4000 rpm to form a first modification layer. Finally, a silver electrode with a thickness of 130 nanometers is formed on the first modification layer by an evaporation method to prepare a perovskite battery. Figure 8 As shown, the power conversion efficiency (PCE) of the perovskite cell formed in this example is 21.41%, and the open circuit voltage (V OC ) is 0.85V, the short-circuit current (J SC ) is 32.82 mA / cm 2 , the fill factor (FF) is 76.32%. Compared with the perovskite battery in the comparative example, the performance of the perovskite battery prepared in this example is significantly improved.
[0118] In addition, if Fig. 9 As shown, it is a comparison chart of the power conversion efficiency of the perovskite battery prepared by a specific example of the present invention and the comparative example. It can be seen from the figure that the power conversion efficiency of the perovskite battery formed after formic acid is introduced in the preparation process of the first hole transport layer of the present invention is significantly higher than that of the perovskite battery of the comparative example in which formic acid is not introduced.
[0119] Embodiment 2
[0120] This embodiment provides a method for preparing a perovskite battery. The method for preparing a perovskite battery in this embodiment is basically the same as the method for preparing a perovskite battery in Example 1, except that before forming the first hole transport layer 112, it also includes a step of forming a top battery structure layer 12 on the conductive substrate 111, and the PEDOT:PSS solution and acid solution are coated on the surface of the top battery structure layer 12.
[0121] As an example, the formation of the top battery structure layer 12 includes the following steps:
[0122] (1) Please refer to Fig.10 , forming a second hole transport layer 121 on the conductive substrate 111;
[0123] As an example, forming the second hole transport layer 121 includes the following steps:
[0124] (1.1) preparing a nanoparticle precursor solution of a certain concentration, and coating the nanoparticle precursor solution on the conductive substrate 111;
[0125] (1.2) Perform annealing treatment.
[0126] As an example, a coating method of coating the nanoparticle precursor solution on the conductive substrate 111 includes any one of spray coating, spin coating, drop coating, doctor blade coating, roller coating and air knife coating.
[0127] As an example, the concentration range of the nanoparticle precursor solution is 5 to 25 mg / ml.
[0128] As an example, the material of the second hole transport layer 121 includes any one of nickel oxide (NiO), vanadium pentoxide (V2O5), copper iodide (CuI), molybdenum trioxide (MoO3), copper oxide (CuO) and cuprous oxide (Cu2O).
[0129] In a specific example, forming the second hole transport layer 121 includes the following steps:
[0130] (1.1) dropping 60 μL of NiO nanoparticle precursor solution onto the surface of the conductive substrate 111, and spin coating the NiO nanoparticle precursor solution at a rotation speed of 3000 rpm, so that the NiO nanoparticle precursor solution is evenly distributed on the conductive substrate 111, wherein the NiO nanoparticle precursor solution is prepared by dissolving NiO nanoparticles in deionized water at a concentration of 15 mg / ml;
[0131] (1.3) In air, the conductive substrate 111 coated with the NiO nanoparticle precursor solution is annealed at 150° C. for 10 minutes to form a NiO hole transport layer. After the annealing is completed, the conductive substrate 111 is immediately transferred to a glove box.
[0132] (2) See also Fig.10 , forming an interface modification layer 122 on the second hole transport layer 121 .
[0133] As an example, forming the interface modification layer 122 includes the following steps:
[0134] (2.1) preparing an interface modification pre-coating solution;
[0135] (2.2) coating the interface modification pre-coating liquid on the second hole transport layer 121;
[0136] (2.3) Perform annealing treatment.
[0137] As an example, a coating method of coating the interface modification pre-coating liquid on the second hole transport layer 121 includes any one of spray coating, spin coating, drop coating, doctor blade coating, roller coating and air knife coating.
[0138] As an example, the interface modification layer 122 is a self-assembled molecular layer, and the material of the interface modification layer 122 includes at least one of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz).
[0139] In a specific example, forming the interface modification layer 122 includes the following steps:
[0140] (2.1) Dissolving 2PACz and MeO-2PACz in isopropyl alcohol (IPA) respectively to form a first solution containing 2PACz and a second solution containing MeO-2PACz, wherein the concentrations of the first solution and the second solution are both 0.001 mol / L. Then, the first solution and the second solution are mixed at a volume ratio of 75:25 to form the interface modification pre-coating solution;
[0141] (2.2) dropping the interface modification pre-coating liquid onto the second hole transport layer 121, and spin coating the interface modification pre-coating liquid at a rotation speed of 6000 rpm for 30 seconds, so that the interface modification pre-coating liquid is evenly distributed on the second hole transport layer 121;
[0142] (2.3) An annealing treatment is performed at a temperature of 150° C. for 10 minutes to form the interface modification layer 122 .
[0143] (3) Please continue reading Fig.10 , prepare a perovskite precursor solution of a certain concentration, apply the perovskite precursor solution on the interface modification layer 122, perform anti-solvent treatment on the perovskite precursor solution, and then perform annealing treatment to form a perovskite thin film layer 123, wherein the bandgap width of the perovskite thin film layer 123 is greater than the bandgap width of the lead-tin perovskite thin film layer 113.
[0144] As an example, preparing the perovskite precursor solution includes the following steps:
[0145] CsI, cesium bromide (CsBr), FAI, PbI2, lead bromide (PbBr2), and formamidine bromide (FABr) were dissolved in a mixed solvent consisting of DMSO and DMF in a volume ratio of 1:4, and stirred until the mixture was uniform to obtain a FA solution with a concentration of 0.5 to 2.5 mol / mL. 0.8 Cs 0.2 Pb(I 0.6 2Br 0.38 )3Perovskite precursor solution.
[0146] As an example, the coating method of coating the perovskite precursor solution on the interface modification layer 122 includes any one of spray coating, spin coating, drop coating, doctor blade coating, roller coating, air knife coating and brush coating.
[0147] As an example, coating the perovskite precursor solution on the interface modification layer 122 and performing anti-solvent treatment on the perovskite precursor solution includes the following steps:
[0148] The perovskite precursor solution is drop-coated on the interface modification layer 122, and spin-coated at a speed of 1500-2500 rpm for 5-15 seconds, and then spin-coated at a speed of 5500-6500 rpm for 30-50 seconds, and an anti-solvent is added 5-15 seconds before the end of the coating. The anti-solvent added in this step is the same as the anti-solvent material added when the lead-tin perovskite precursor solution is subjected to anti-solvent treatment in Example 1.
[0149] As an example, the temperature range of the annealing treatment performed after the anti-solvent treatment of the perovskite precursor solution is 50 to 150° C., and the time range of the annealing treatment is 10 to 20 minutes.
[0150] In a specific example, the perovskite thin film layer 123 is formed by the following steps:
[0151] (3.1) Preparation of FA 0.8 Cs 0.2 Pb(I 0.6 2Br 0.38 )3 perovskite precursor solution, the FA 0.8 Cs 0.2 Pb(I 0.6 2Br 0.38 )3 Perovskite precursor solution is prepared by dissolving CsI, CsBr, FAI, PbI2, PbBr2, and FABr in a mixed solvent consisting of 0.2 mL of DMSO and 0.8 mL of DMF, and stirring for 2 hours to mix uniformly, wherein the FA 0.8 Cs 0.2 Pb(I 0.6 2Br0.38 )3The concentration of the perovskite precursor solution is 1.2 mol / mL.
[0152] (3.2) The FA 0.8 Cs 0.2 Pb(I 0.6 2Br 0.38 )3 The perovskite precursor solution is drop-coated on the interface modification layer 122 and spin-coated at a speed of 2000 rpm for 10 seconds to make the FA 0.8 Cs 0.2 Pb(I 0.6 2Br 0.38 )3 The perovskite precursor solution evenly covers the surface of the interface modification layer 122. Afterwards, the rotation speed is increased to 6000 rpm and continued to rotate for 40 seconds. When the rotation reaches 30 seconds, 200 μL of anti-solvent (chlorobenzene) is added dropwise for anti-solvent treatment.
[0153] (3.3) The conductive substrate 111 is transferred to a hot plate and heated at 100° C. for 15 minutes to perform an annealing process to form the perovskite thin film layer 123 .
[0154] (4) Please refer to Fig.10 , forming a second electron transport layer 124 on the perovskite thin film layer 123 .
[0155] Specifically, the method of forming the second electron transport layer 124 includes thermal evaporation, atomic layer deposition, spin coating, doctor blade coating, slit deposition, spray coating, chemical bath deposition or other suitable methods.
[0156] As an example, the material of the second electron transport layer 124 includes BCP, C 60 , PCBM, TiO2, SnO2 and SrTiO3.
[0157] As an example, the thickness of the second electron transport layer 124 is in the range of 2 to 30 nanometers.
[0158] In a specific example, a 15 nm thick C layer is deposited on the perovskite thin film layer 123 by thermal evaporation. 60 A thin film is formed to form the second electron transport layer 124 .
[0159] (5) Please refer to Fig.10 , forming an interconnection layer 126 on the second electron transport layer 124 .
[0160] As an example, a second modification layer 125 is further formed between the second electron transport layer 124 and the interconnect layer 126 .
[0161] As an example, the method of forming the second modification layer 125 includes any one of atomic layer deposition, spin coating, doctor blading, slit deposition, spray coating, evaporation, magnetron sputtering, electrochemical deposition and chemical bath deposition.
[0162] As an example, the material of the second modification layer 125 includes SnO x , where the value range of X is 1 to 2.
[0163] Specifically, in this embodiment, an atomic layer deposition method is used to deposit a SnO 2 thin film at a temperature of 120° C. to form the second modification layer 125 .
[0164] Specifically, the method of forming the interconnection layer 126 includes magnetron sputtering, evaporation, physical vapor deposition, chemical vapor deposition, metal compound vapor deposition, molecular beam epitaxy, atomic vapor deposition, atomic layer deposition or other suitable methods.
[0165] As an example, the material of the interconnection layer 126 includes any one of gold, silver, aluminum, copper, nickel, carbon, and ITO.
[0166] As an example, the thickness of the interconnect layer 126 is in the range of ≤ 3 nanometers.
[0167] Specifically, in this embodiment, a gold film with a thickness of 1 nanometer is deposited on the second modification layer 125 by evaporation to form the interconnection layer 126 .
[0168] At this point, a perovskite battery (laminated perovskite battery 1) is manufactured. Fig.10 shown.
[0169] This embodiment achieves optimized superposition of perovskite layers with different band gaps by setting a top battery structure layer 12 between the conductive substrate 111 and the first hole transport layer 112, thereby expanding the spectral absorption range of the perovskite battery and reducing thermal relaxation losses, thereby forming an efficient stacked perovskite battery structure. Among them, the lead-tin perovskite battery 11 serves as a bottom battery and has a narrow band gap; the top battery structure layer 12 serves as a top battery and has a wide band gap. During the preparation process of the lead-tin perovskite battery 11, an acid solution is introduced to form a first hole transport layer 112 with optimized energy levels. This step effectively improves the power conversion efficiency of the lead-tin perovskite battery 11, thereby enhancing the performance of the entire stacked perovskite battery 1. It should be noted that Fig.10 The structural order in the figure is for schematic display and should be reversed in actual application, that is, the bottom battery is located at the lower layer and the top battery is located at the upper layer to ensure the correct function of the battery structure and achieve optimal performance.
[0170] Embodiment 3
[0171] The present embodiment provides a perovskite battery structure, and the perovskite battery structure is obtained by the preparation method of any one of the perovskite batteries in Example 1 and Example 2. In the perovskite battery structure of this embodiment, the lead-tin perovskite film layer exhibits excellent crystal quality, and the surface of the film layer is flat and uniform without obvious defects. These characteristics significantly improve the photoelectric conversion efficiency of the perovskite battery. In addition, the perovskite battery achieves high compatibility with the lead-tin perovskite film layer by optimizing the energy level structure of the first hole transport layer, further optimizing the extraction and transmission of charges, thereby effectively improving the power conversion efficiency of the battery.
[0172] In summary, the present invention provides a method for preparing a perovskite battery and its structure, which not only achieves the optimization treatment of the PEDOT:PSS hole transport layer by adding acid during the formation of the first hole transport layer, but also enhances the compatibility of the first hole transport layer with the upper lead-tin perovskite film layer, and significantly optimizes the crystal crystallinity and crystal orientation of the lead-tin perovskite film layer, eliminating the problems of excessive gaps between crystals, small grains, and poor crystallinity after perovskite crystallization caused by the presence of impurities or excessive lead iodide and tin iodide, thereby effectively improving the power conversion efficiency of the perovskite battery. The preparation method of the present invention is simple and easy, significantly improves the overall performance of the perovskite battery, and can be widely used in photovoltaic power generation, photoelectric detection and other fields. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.
[0173] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a perovskite battery, characterized in that: The following steps are involved: Providing a conductive substrate, and pre-treating the conductive substrate; Applying the PEDOT:PSS solution and the acid solution separately or pre-mixing them on the conductive substrate, and performing annealing treatment to form a first hole transport layer; A lead-tin perovskite precursor solution of a certain concentration is prepared, the lead-tin perovskite precursor solution is coated on the first hole transport layer, and the lead-tin perovskite precursor solution is subjected to an anti-solvent treatment, and then an annealing treatment is performed to form a lead-tin perovskite thin film layer; forming a first electron transport layer on the lead-tin perovskite thin film layer; A metal electrode layer is formed on the first electron transport layer.
2. The method for preparing a perovskite battery according to claim 1, characterized in that: The PEDOT:PSS solution and the acid solution are coated on the conductive substrate in a pre-mixed manner, wherein the acid solution is added to the PEDOT:PSS solution in a preset ratio to form a mixed solution, and then the mixed solution is coated on the conductive substrate.
3. The method for preparing a perovskite battery according to claim 1, characterized in that: The PEDOT:PSS solution and the acid solution are coated on the conductive substrate in a separate application manner, wherein after the PEDOT:PSS solution is coated on the conductive substrate, the acid solution is applied on the conductive substrate coated with the PEDOT:PSS solution.
4. The method for preparing a perovskite battery according to claim 1, characterized in that: The acid solution includes any one of formic acid, acetic acid, oxalic acid, citric acid, malic acid, crotonic acid and caffeic acid.
5. The method for preparing a perovskite battery according to claim 1, characterized in that: A first passivation layer is also formed between the lead-tin perovskite thin film layer and the first electron transport layer.
6. The method for preparing a perovskite battery according to claim 1, characterized in that: A first modification layer is also formed between the first electron transport layer and the metal electrode layer.
7. The method for preparing a perovskite battery according to claim 1, characterized in that: Before forming the first hole transport layer, the method further includes forming a top battery structure layer on the conductive substrate, and the PEDOT:PSS solution and the acid solution are coated on the surface of the top battery structure layer.
8. The method for preparing a perovskite battery according to claim 7, characterized in that: The formation of the top battery structure layer comprises the following steps: forming a second hole transport layer on the conductive substrate; forming an interface modification layer on the second hole transport layer; A perovskite precursor solution of a certain concentration is prepared, the perovskite precursor solution is coated on the interface modification layer, the perovskite precursor solution is subjected to an anti-solvent treatment, and then an annealing treatment is performed to form a perovskite thin film layer, wherein the band gap width of the perovskite thin film layer is greater than the band gap width of the lead-tin perovskite thin film layer; forming a second electron transport layer on the perovskite thin film layer; An interconnection layer is formed on the second electron transport layer.
9. The method for preparing a perovskite battery according to claim 8, characterized in that: A second modification layer is also formed between the second electron transport layer and the interconnect layer.
10. A perovskite battery structure, characterized in that: The perovskite battery structure is obtained by using the preparation method of the perovskite battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Tin-based perovskite thin film, quality improvement method thereof and tin-based perovskite solar cell
CN113410400A
Optimized crystallization method for hole transport layer of flexible high-efficiency large-area perovskite solar cell
CN117794333A
Hole transport layer material, laminated perovskite solar cell and preparation method
CN117835782A
Hole transport layer and preparation method and application thereof
CN118317615A